구리전해도금에서 폴리에틸렌글리콜(polyethylene glycol)의 영향 연구 - 안의경; 최선기; 이재원; 조성기; An, Eui Gyeong; Choi, Sun Gi; Lee, Jaewon; Cho, Sung Ki (전기화학회지, 2022)
In this study, the effect of polyethylene glycol (PEG) on Cu electrodeposition was analyzed using cyclic voltammetry. The adsorption of PEG was affected by the specific adsorption of sulfate ion (SO42-) or chloride ion (Cl-). In SO42--based plating solution, the adsorption of PEG was limited by the adsorbed SO42-. Accordingly, the adsorbed PEG could suppress the electron transfer for Cu electrodeposition, but its effect was not significant. Meanwhile, in the plating solution composed of perchlorate ion (ClO4-) which does not specifically adsorb on Cu surface, a strong suppression effect of PEG was observed and it was proportional to the molecular weight of PEG. On the other hand, when Cl- was specifically adsorbed on Cu surface, the suppression effect of PEG was enhanced because PEG and Cl- formed an interrelated adsorbate. The synergetic effect of PEG and Cl- depended on the composition of the plating solution, which means that the synergy between PEG and Cl- is based on the physical interaction. For example, the hydrophobicity of PEG plays an important role in the interaction, as the suppression effect of PEG derivative having a hydrocarbon tail was further enhanced with the addition of Cl-. 본 연구에서는 polyethylene glycol (PEG)이 구리전해도금에 미치는 영향을 cyclic voltammetry를 이용해 분석해보았다. PEG의 흡착은 함께 존재하는 음이온의 특이흡착에 따라 변화되었다. 가장 일반적인 도금액 성분인 sulfate 이온(SO42-)이 존재하는 경우, PEG의 흡착이 억제되었으며 그로 인해 미약한 억제 효과가 관찰되었다. 실제로 도금액이 SO42- 없이 특이흡착하지 않는 perchlorate 이온(ClO4-)으로만 이뤄진 경우, PEG는 도금 반응을 강하게 억제하였으며 억제 효과는 PEG의 분자량에 비례하여 나타났다. 반면, 염소 이온(Cl-)의 특이흡착이 존재하는 경우 오히려 PEG의 억제 효과는 강화되었다. RDE 분석을 통해 강한 억제 효과는 PEG와 Cl-간의 흡착구조체 형성에 의한 것임을 확인하였으며, 이러한 흡착 구조체 형성은 용액 조성에 따라 달라지는 특성을 나타내었다. 특히, 소수성 특성이 증가된 PEG 유도체의 경우 억제 효과가 더욱 강화되는 것으로 미루어, PEG와 Cl-간의 흡착 구조체 형성에 PEG의 소수성 특성이 중요함을 확인하였다.